Convenient chromatography-free access to enantio-pure 6,6’-di-tert-butyl-1,1’- binaphthalene-2,2’-diol- its 3,3’-dibromo, di-tert-butyl and phosphorus derivatives: utility in asymmetric synthesis - Balaraman, Ekambaram; Swamy, K. C. Kumara (Tetrahedron-Asymmetry, 2007)
A simple chromatography-free high-yielding synthesis of the hexane-soluble enantiopure 6,6′-di-tert-butyl-1,1′-binaphthalene-2,2′-diol 3 (6,6′-di-tert-butyl BINOL) using Friedel–Crafts reaction on 1,1′-binaphthalene-2,2′-diol 1 (BINOL) is described. The enantiomeric purity was fully maintained in the reaction. Compound 3 has been used as an entry point for the convenient chromatography-free synthesis of 3,3′,6,6′-tetra-tert-butyl BINOL 4 and 3,3′-dibromo-6,6′-di-tert-butyl BINOL 5. A straightforward route to enantiopure bisphosphites [(6,6′-R2C20H10O2)P]2[O2C20H10-6,6′-R2] [R = H 15, t-Bu 16] by simply reacting phosphorochloridite (6,6′-R2C20H10O2)PCl [R = H 20, t-Bu 6] with metallic sodium is highlighted. The identity of 15 and 16 as their selenium-oxidized products 17 and 18 (at phosphorus center) is confirmed by X-ray crystallography (17 in the enantiopure form and 18 as racemate). Various enantiopure phosphoramidites of the modified BINOL have been synthesized. It is established that even when the phosphoramidites derived from the unsusbstituted BINOL 1 fail to give an appreciable optical induction in the asymmetric reduction of acetophenone/phenacyl chloride, those derived from 3 do induce moderate chiral induction (up to 30% ee in the case for acetophenone and 43% ee in the case of phenacyl chloride), thus leaving scope for further improvement in ee for related reactions.